Pengaruh Motivasi, Biaya Pendidikan Dan Lama Masa Studi Pada Minat Mahasiswa Mengikuti PPAk - Widiyani, Ni Luh Ira Apri; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2019)
This research was conducted at the Faculty of Economics and Business, Udayana University. The sample in this study is the 2016 non-regular program accounting students. The number of samples used was 60 respondents who were determined using a non probability sampling method with a purposive sampling technique.. The results of the study found that quality motivation, social motivation, economic motivation had a positive effect on students' interest in participating in PPAk. This means that the better the motivation will increase the interest of students in participating in PPAk. The cost of education and the length of the study period have a positive effect on students' interest in joining PPAk. This means that the more appropriate the cost of education and the length of the study period will increase students' interest in joining PPAk. Keywords : Motivation; Tuition Fee; Length Of Study Period; Interest In Students Participating in PPAk.